Between Nationalism and Universalism: Qatar 2022 World Cup and Investment in Sustainability and Nation Branding in Light of the Goals of Sharia - Almulla, Salwa Hamed (Journal of Contemporary Maqasid Studies, 2024)
Countries strive to highlight their national identities and cultural heritage, particularly in Sports Mega Event (SME). This study sheds light on Qatar 2022 World Cup experience, in which Qatar highlighted the Qatari national identity and its Gulf/Arab/Islamic elements, by studying the media propaganda against the Qatar 2022 bid and questioning its content alongside revealing the extent to which it was credible, particularly because the Qatari identity was a prominent factor in the championship. The study covers a timeframe from December 2010, when Qatar received the right to host the World Cup, through the years of preparation and planning, to the organization stage, which began on November 20th and continued until December 2022. Through descriptive and analytical study, the study seeks to highlight the Qatari experience in preserving its Arab and Islamic identity, achieving sustainability, and managing World Cup security in a way that is complied with the goals of Islamic Sharia. It also compares various international experiences in the field to accurately evaluate the Qatari experience. The findings of the study reveal Qatar succeeded in promoting the Qatari Islamic and national identity via banning liquors and homosexualism and fulfilled its overlapping economic and social goals reflected in the growth of Qatari economy and the growing perception of Qatar as a safe and attractive venue worthy of visits and investment. These findings are in line with Maqasid Shariah and present recommendations to organizing bodies globally on how to achieve positive aspects in SME and leverage in similar experiences.